Dynamic Action Potential Restitution Contributes to Mechanical Restitution in Right Ventricular Myocytes From Pulmonary Hypertensive Rats - Hardy, Matthew E. L.; Pervolaraki, Eleftheria; Bernus, Olivier; White, Ed (Frontiers in Physiology, 2018)
We investigated the steepened dynamic action potential duration (APD) restitution of rats with pulmonary artery hypertension (PAH) and right ventricular (RV) failure and tested whether the observed APD restitution properties were responsible for negative mechanical restitution in these myocytes. PAH and RV failure were provoked in male Wistar rats by a single injection of monocrotaline (MCT) and compared with saline-injected animals (CON). Action potentials were recorded from isolated RV myocytes at stimulation frequencies between 1-9 Hz. Action potential waveforms recorded at 1Hz were used as voltage clamp profiles (action potential clamp) at stimulation frequencies between 1-7 Hz to evoke rate-dependent currents. Voltage clamp profiles mimicking typical CON and MCT APD restitution were applied and cell shortening simultaneously monitored. Compared with CON myocytes, MCT myocytes were hypertrophied; had less polarized diastolic membrane potentials; had action potentials that were triggered by decreased positive current density and shortened by decreased negative current density; APD was longer and APD restitution steeper. APD90 restitution was unchanged by exposure to the late Na+-channel blocker (5 µM) ranolazine or the intracellular Ca2+ buffer BAPTA. Under AP clamp, stimulation frequency-dependent inward currents were smaller in MCT myocytes and were abolished by BAPTA. In MCT myocytes, increasing stimulation frequency decreased contraction amplitude when depolarization duration was shortened, to mimic APD restitution, but not when depolarization duration was maintained. We present new evidence that the membrane potential of PAH myocytes is less stable than normal myocytes, being more easily perturbed by external currents. These observations can explain increased susceptibility to arrhythmias. We also present novel evidence that negative APD restitution is at least in part responsible for the negative mechanical restitution in PAH myocytes. Thus our study links electrical restitution remodelling to a defining mechanical characteristic of heart failure, the reduced ability to respond to an increase in demand.